2014
DOI: 10.3109/10253890.2014.898059
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced endocrine response and anxiety: the effects of comfort food in rats

Abstract: The long-term effects of comfort food in an anxiogenic model of stress have yet to be analyzed. Here, we evaluated behavioral, endocrine and metabolic parameters in rats submitted or not to chronic unpredictable mild stress (CUMS), with access to commercial chow alone or to commercial chow and comfort food. Stress did not alter the preference for comfort food but decreased food intake. In the elevated plus-maze (EPM) test, stressed rats were less likely to enter/remain in the open arms, as well as being more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 52 publications
2
15
0
6
Order By: Relevance
“…To evaluate the experimental data, a two-way (restraint stress × gestational age) analysis of variance (ANOVA) was performed, followed by a Duncan posthoc test. The significant difference between control and stressed mice at a given gestational age was evaluated using Independent-samples t-test (Ortolani et al, 2014). In the data for food intake, n was the number of cages per group, while n was the number of mice per group for the other data collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the experimental data, a two-way (restraint stress × gestational age) analysis of variance (ANOVA) was performed, followed by a Duncan posthoc test. The significant difference between control and stressed mice at a given gestational age was evaluated using Independent-samples t-test (Ortolani et al, 2014). In the data for food intake, n was the number of cages per group, while n was the number of mice per group for the other data collected.…”
Section: Discussionmentioning
confidence: 99%
“…Restraint stress during late gestation decreases body weight and food intake of the dams, and produces long-term metabolic changes (Mairesse et al, 2007). Moreover, restraint stress not only decreases food consumption (Ortolani et al, 2014), but also increases appetite for sweet food in rodents (Ely et al, 1997). Generally, maternal weight increases with increase in gestational age.…”
Section: Restraint Stress Decreased Body and Organ Weightmentioning
confidence: 98%
“…The data were analyzed with SPSS 18.0 (SPSS Inc., Chicago, IL) as described in a previous study (Ortolani et al, 2014). To analyze the effects of restraint stress and different gestational stages on the experimental data, a two-way analysis of variance (ANOVA) was performed followed by Duncan's post hoc test.…”
Section: Discussionmentioning
confidence: 99%
“…A number of chronic stress models including chronic mild, chronic variable, social instability, and social isolation have been used in female rats. Many of these studies report increased anxiety‐like behaviors in traditional behavioral assays including the elevated plus maze and open field (Haller et al, ; Dalla et al, ; Ortolani et al, ) and depression‐like behavior as indicated by decreased sucrose consumption and/or increased immobility in the forced swim test (Baker et al, ; Bourke and Neigh, ). In contrast, far fewer studies have investigated the impact of chronic stressors on subsequent social behavior in female rats.…”
Section: Introductionmentioning
confidence: 99%